THE FACTORS THAT EFFECT ON INTERNAL AUDITOR INDEPENDENCE IN THE ACEH BANKING SECTOR - Nasvita, Dwi Meilvi (SCAD Independent, 2016)
This study aimed to examine the factors that effect on internal auditor independence of the internal auditor, namely the competence of internal auditors, management intervention, employee participation and regulation of the company. The sample of this research is internal auditing staff at banks of Aceh. Data were collected through the distribution of questionnaires to respondents using multiple linear regression analysis. The results showed that all factors have influences on the independence of internal auditor, simultaneously or partially. While auditor competence, employee participation, and company regulation have positive influence, management intervention has a negative influence on the independence of the internal auditors.